INTERAKSI SOSIAL PADA MASYARAKAT BEDA AGAMA DALAM PERSPEKTIF KOMUNIKASI ANTARBUDAYA DI KOTA TUA AMPENAN MATARAM - Muhammad Yasin Isa Al-Gazali (JURNAL ILMIAH GLOBAL EDUCATION, 2022)
This study aims to describe and explain the condition of the people in Banjar Village, Central Ampenan District, Mataram City which is related to social interaction in people of different religions in the perspective of intercultural communication. In addition, this study aims to determine the extent to which cultural values ​​and norms can affect inter-religious harmony in Ampenan and to find out what factors support and hinder harmony between people of different religions in Banjar Village, Ampenan Tengah District, Mataram.This research is a qualitative research, data collection is done by conducting observations or observations, and interviews. The data analysis used is descriptive qualitative data analysis, namely by means of analysis that tends to use words to explain the findings or data obtained in the research field. From the results of this research conducted in the field, it was found that the form of intercultural communication as a process of acculturation and cultural assimilation that occurred in Banjar Village, Ampenan Tengah District between Muslims and other religions was communication between different cultures and until now they have lived side by side and in harmony without any conflict. whatever the background conflicts due to differences in religion and belief, respect each other's culture. The inhibiting and supporting factors for the creation of intercultural communication are cultural factors that are different but mutually respect one another, language factors that have various forms and communication skills factors.